Analysis on National Strategies for Prevention and Control of Antimicrobial Resistance: Learning from Other Countries’ Experiences - Sommanustweechai, Angkana; Sumpradit, Nithima; Patcharanarumol, Walaiporn; Tangcharoensathien, Viroj (Journal of Health Science of Thailand, 2017)
Antimicrobial resistance (AMR) becomes a major public health and human security threat nowadays. It is a complex problem which links people, animals and environment. We reviewed the policy contents in the National Strategic Plan for the prevention and control of AMR in four countries including Australia, Germany, United Kingdom and the United States, with an objective to draw lessons for the development of Thailand National AMR Strategic Plan. The results showed that all strategic plans provide clear directions of actions to tackle AMR. Six key components were identified including raising awareness and understanding on AMR, rational antibiotic use, prevention and control of infection, research and development, surveillance and monitoring, and collaboration, all encompassed the human and animal health sectors. The factors contributing to development of national strategic plan included strong political commitment, integrating collaboration and actions across sectors and stakeholders.